Kosova’s Goddess on the Throne: Critical Fabulation as an Anthropological Method - Drita Bruqi Kabashi (Kosova Anthropologica)
In this article, I describe one of the objects I encountered while working briefly in the National Museum of Kosova: the Goddess on the Throne. In addition to being an important Neolithic artifact, this enigmatic figurine has become the symbol of Prishtina, Kosova. Empirical evidence from the Balkan Neolithic can help theorize aspects of the goddess’s usage and meaning, but little can be known definitively (for example, the perceived gender of the figurine). Nevertheless, I aim to track how it could have been used then, and how it is being used now. Paradoxically, the figurine’s significance and meaning (as a “goddess” deity) exist in direct contrast to the lived reality of contemporary Kosovar women. My case study invokes the material object as agent of its own narration through tracking historical processes that destabilize notions of linear time, connecting the past to the present in interesting, sometimes disconcerting, ways. I use the method of critical fabulation, specifically the medium of poetry, to reveal key points of rupture surrounding the goddess’s role as a modern symbol, but also to demonstrate how poetic exercises can serve as alternatives to museum labels. This approach aims to decenter fixed notions of cultural identity, femininity, and time, and recenter the valuable contradictions that live within the elevated status of certain cultural icons.